Analysis of appeals against the ruling of occupational physicians lodged with the Prevention and Occupational Epidemiology Operative Unit, ASP Palermo (Palermo Health Authority), from 2008-2010 / Analisi dei ricorsi “avverso giudizio del medico... - Firenze, Alberto; Marsala, Maria Grazia Laura; Morici, Maria Grazia; Anastasi, Giovanna; Costantino, C.; Tramuto, F.; Lacca, G.; Curcurù, Loredana; Castagliola, E.; Ilardo, Sara; Trapani, Elisa; Caracausi, Rosa (La Medicina del Lavoro, 2013)
Introduction: The responsibility of the Department for Prevention and Safety at the workplace of the Palermo Health Authority (ASP) is to monitor and coordinate the activity of occupational physicians operating in Palermo and its province. One of its obligations is to examine appeals “against the judgment of occupational physicians”, “...and, after carrying out further investigation, confirm, modify or reverse the ruling itself ” (art. 41, par. 6, legislative Decree 81/08). Objectives: The purpose of this study was to analyze the appeals lodged against a “judgment of fitness for work” submitted to the “Health Prevention and Occupational Epidemiology Operative Unit” of the Department of Prevention and Safety at the Workplace of the ASP Palermo, from 2008 to 2010.Methods: The total number of appeals lodged during the three-year period was 211, 174 of which were finalized. Results: The most frequent job category among the appellants was that of blue-collar workers, in various sectors, covering 44.5% of the subjects under study (93 cases). In 64.2% of the processed appeals (131 cases), the judgment of the physician was modified, while in the remaining 36.8% (73 cases) it was confirmed.The work fitness judgment with restrictions was the category against which most appeals were lodged, and the diseases in question mostly concerned the osteoarticular and cardiovascular systems. Conclusion: In a context of continuous change in the labour field and the related risks to the health and safety of workers, the occupational physician must approach the worker in a comprehensive manner, through an assessment of the possible health problems and the working environment in which he/she operates.  Analisi dei ricorsi “avverso giudizio del medico competente” inoltrati all’U.O.S. “Prevenzione sanitaria e epidemiologia occupazionale” dell’ASP di Palermo nel periodo 2008-2010.Introduzione: Il Servizio di Prevenzione e Sicurezza negli Ambienti di Lavoro” dell’ASP di Palermo ha il compito di controllare e coordinare l’attività dei medici competenti che operano sul territorio di Palermo e Provincia. Tra gli adempimenti istituzionali del servizio è contemplato anche quello di esaminare i ricorsi “avverso giudizio del medico competente” “…disponendo dopo eventuali ulteriori accertamenti, la conferma, la modifica o la revoca del giudizio stesso”(art 41, comma 6 D.Lgs.81/08). Obiettivi: Lo scopo dell’analisi è l’esame dei ricorsi “avverso giudizio di idoneità” pervenuti all’UOS “Prevenzione Sanitaria e Epidemiologia Occupazionale” del Servizio di Prevenzione e Sicurezza negli Ambienti di Lavoro” del dipartimento di prevenzione dell’ASP di Palermo dal 2008 al 2010. Metodi: Il numero totale dei ricorsi pervenuti nel triennio è di 211, di cui ne sono stati espletati 174. Risultati: La qualifica dei ricorrenti in assoluto più numerosa è quella di operaio impegnato in diversi settori lavorativi, rappresentando il 44.5% (n. 93)del campione totale. Nel 64.2% (n. 131) dei ricorsi esitati è stato modificato il giudizio del medico, mentre nel 36.8% (n. 73) dei casi il giudizio è stato confermato. Il giudizio di idoneità con limitazioni è quello per cui viene più frequentemente presentato il ricorso e le patologie da cui sono affetti i lavoratori in esame riguardano principalmente l’apparato osteoarticolare e le malattie cardiovascolari. Conclusioni: In un contesto di cambiamento continuo del mondo del lavoro e dei relativi rischi per la salute e la sicurezza dei lavoratori, il medico competente deve approcciarsi al lavoratore in maniera globale, mediante una valutazione delle eventuali problematiche di salute e del contesto lavorativo in cui opera.